Male Dominant Enrollment among Physical Education Majors. An Analysis Based on Gender Perspective - Matus Castillo, Carlos (2021)
Chile has not yet conducted studies on physical education teacher training programs which examine enrollment trends for that college major based on a gender approach. This study examines female and male enrollment trends for physical education teacher training programs throughought Chile´s universities. The study was executed using a quantitative approach with a non-experimental, retrospective and exploratory-descriptive design. Data pertaining to college training programs spanning 2005 to 2109 was used from official open-access sources. Study results of the study, reveal a reduction in the number of women that enroll to become PE Teacher-Training majors, thereby emphasizing a significant gender gap inconsistent with teacher training programs in other disciplines as well as student university enrollment, in general. This is a distinct reflection of the persistence of masculine hegemony in physical education teacher training programs in Chile.